2017
DOI: 10.1080/00150193.2017.1370266
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition and energy storage properties of BaTiO3-modified Bi0.5(Na0.8K0.2)0.5TiO3 ceramics

Abstract: Electrical energy storage systems (EESSs) with high energy density and power density are essential for the effective miniaturization of future electronic devices. Among different EESSs available in the market, dielectric capacitors relying on swift electronic and ionic polarization-based mechanisms to store and deliver energy already demonstrate high power densities. However, different intrinsic and extrinsic contributions to energy dissipations prevent ceramic-based dielectric capacitors from reaching high re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 187 publications
(246 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, to synthesize piezoceramic composites for obtaining MPB (morphotropic phase boundary) with relaxor-ferroelectric behavior, a wide range of additional perovskites may be easily diffused into this compound. According to the previous study on Bi–Na–K–TiO 3 , the dielectric constant ε = ∼3750 at temperature T m , P max = ∼30 μC/cm 2 , W rec = ∼110 mJ/cm, and η% = ∼20% at a biasing field of 50 kV/cm . Schader et al suggested the confinement of the coexistence of ergodic and non-ergodic relaxor (NR-ER) sections of the BNT–BT materials near the MPB during the phase transition from the ferroelectric to the relaxor ferroelectric .…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, to synthesize piezoceramic composites for obtaining MPB (morphotropic phase boundary) with relaxor-ferroelectric behavior, a wide range of additional perovskites may be easily diffused into this compound. According to the previous study on Bi–Na–K–TiO 3 , the dielectric constant ε = ∼3750 at temperature T m , P max = ∼30 μC/cm 2 , W rec = ∼110 mJ/cm, and η% = ∼20% at a biasing field of 50 kV/cm . Schader et al suggested the confinement of the coexistence of ergodic and non-ergodic relaxor (NR-ER) sections of the BNT–BT materials near the MPB during the phase transition from the ferroelectric to the relaxor ferroelectric .…”
Section: Introductionmentioning
confidence: 96%
“…According to the previous study on Bi−Na−K−TiO 3 , the dielectric constant ε = ∼3750 at temperature T m , P max = ∼30 μC/cm 2 , W rec = ∼110 mJ/cm, and η% = ∼20% at a biasing field of 50 kV/cm. 7 Schader et al suggested the confinement of the coexistence of ergodic and non-ergodic relaxor (NR-ER) sections of the BNT−BT materials near the MPB during the phase transition from the ferroelectric to the relaxor ferroelectric. 8 Thus, bismuth (Bi)-based perovskite structure piezoceramics such as Bi−Na−K−TiO 3 , Bi−Na−TiO 3 , BiFeO 3 , and so forth have generated a great interest in the scientific community for research on them for piezoelectric applications.…”
Section: Introductionmentioning
confidence: 99%
“…One study reported on the co‐doping of the A and B‐site in the BNKT system and performed a comparative analysis of the structure‐property relationships 6 . In other studies, additives such as BaTiO 3 , 7 KNN, 8 BZT, 9 and BiAlO 3 10 were added to the BNKT system. These ternary systems have shown improved electrical performance and are easier to pole relative to the unmodified BNKT system.…”
Section: Introductionmentioning
confidence: 99%